PENGARUH PERCEIVED QUALITY DAN ETNOSENTRISME KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK J.CO DONUTS AND COFFEE DI KOTA PONTIANAK - B11110024, Zamiil Solihin (Jurnal Manajemen Update, 2015)
This researchaimed to analyze the influence of perceived quality and ethnocentrisme consumers on buying decisions on products J.CO Donuts and Coffee in Pontianak. This research uses quantitative methods and causal descriptive form. The population in this study is a society of Pontianak city that became consumers J.CO Donuts and Coffee. This research was used purposive sampling, then selected 100 people. The analysis technique used is multiple linear regression analysis by using SPSS version 20.0. The results of the analysis of the data obtained showed that the perceived quality and ethnocentrisme consumer significant effect on product buying decisions J.CO Donuts and Coffee among the people of the city of Pontianak, with a significance value of 0.000 and R2 value of 33.8%, while the remaining 66.2% are other factors not examined in this research. Keyword : perceived quality, ethnocentrisme consumer, and buying decision